Challenges of transitioning from a faculty to an administrative role: part 3, from solving problems to managing polarities. - Thompson, Cesarina M (Nurse Educator, 2011)
Many new nursing leaders assuming deanships, assistant, or interim deanships have limited education, experience, or background to prepare them for the job. To assist new deans and those aspiring to be deans, Jana L. Pressler, PhD, RN, and Carole A. Kenner, PhD, RNC-NIC, FAAN, the editors of this department, address common issues, challenges, and opportunities that face academic executive teams, such as negotiating an executive contract, obtaining faculty lines, building effective work teams, managing difficult employees, and creating nimble organizational structure to respond to changing consumer, healthcare delivery, and community needs. In this article, the editors asked guest author, Dr Cesarina Thompson, to discuss the transition process from faculty to administrative role.
Keywords: *Education, Nursing; *Efficiency, Organizational; *Faculty, Nursing; *Leadership; *Nurse Administrators; *Professional Role/px [Psychology]; Curriculum; Education, Nursing; Efficiency, Organizational; Faculty, Nursing; Humans; Leadership; Nurse Administrators; Professional Role; Time Factors; article; curriculum; dept.aa; human; leadership; nurse administrator; nursing education; organization and management; peer-reviewed; professional standard; psychological aspect; time